A genome-wide association study on amyotrophic lateral sclerosis in the Taiwanese Han population. (June 2016) - Chen, Chi-Jim; Chen, Chien-Ming; Pai, Tun-Wen; Chang, Hao-Teng; Hwang, Chi-Shin
Identification of mutations in patients with amyotrophic lateral sclerosis (ALS) in a genome-wide association study can reveal possible biomarkers of such a rapidly progressive and fatal neurodegenerative disease. It was observed that significant single nucleotide polymorphisms vary when the tested population changes from one ethnic group to another. To identify new loci associated with ALS susceptibility in the Taiwanese Han population, we performed a genome-wide association study on 94 patients with sporadic ALS and 376 matched controls. We uncovered two new susceptibility loci at 13q14.3 (rs2785946) and 11q25 (rs11224052). In addition, we analyzed the functions of all the associated genes among 54 significant single nucleotide polymorphisms using Gene Ontology annotations, and the results showed several statistically significant neural- and muscle-related Gene Ontology terms and the associated diseases.